Sexual selection in primates (Cambridge University Press, 2004)
Sexual Selection in Primates provides an account of all aspects of sexual selection in primates, combining theoretical insights, comprehensive reviews of the primate literature and comparative perspectives from relevant work on other mammals, birds and humans. Topics include sex roles, sexual dimorphism in weapons, ornaments and armaments, sex ratios, sex differences in behaviour and development, mate choice, sexual conflict, sex-specific life history strategies, sperm competition and infanticide. Sexual Selection in Primates is aimed at graduates and researchers in primatology, animal behaviour, evolutionary biology and comparative psychology.